2018
DOI: 10.1187/cbe.18-02-0022
|View full text |Cite
|
Sign up to set email alerts
|

Student Integration into STEM Careers and Culture: A Longitudinal Examination of Summer Faculty Mentors and Project Ownership

Abstract: It is widely recognized that the United States needs to attract and retain more people in science, technology, engineering, and mathematics (STEM) careers. Intensive undergraduate research experiences (UREs) are one of the few strategies shown to improve longitudinal student interest and persistence in STEM-related career pathways; however, less is known about the underlying process linking activities to positive outcomes. The tripartite integration model of social influences (TIMSI) provides a framework for u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 95 publications
1
45
0
Order By: Relevance
“…Additional studies have examined TIMSI predictions in a more limited fashion, testing TIMSI predictions concerning the relationships between social influence agents, social influence processes, and social integration among college students over a shorter period of time (e.g., a 10-week summer research experience), or focusing more narrowly on TIMSI predictions concerning the relationships between social influence processes and social integration (Social Influence Processes → Social Integration) [ 62 , 64 , 65 ]. The results from these more limited studies provide convergent evidence indicating higher levels of mentorship support lead to higher levels of the efficacy, identity, and values (i.e., social influence processes) and higher levels of social influence processes, particularly science identity, lead to higher levels of persistence [ 62 , 64 , 65 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional studies have examined TIMSI predictions in a more limited fashion, testing TIMSI predictions concerning the relationships between social influence agents, social influence processes, and social integration among college students over a shorter period of time (e.g., a 10-week summer research experience), or focusing more narrowly on TIMSI predictions concerning the relationships between social influence processes and social integration (Social Influence Processes → Social Integration) [ 62 , 64 , 65 ]. The results from these more limited studies provide convergent evidence indicating higher levels of mentorship support lead to higher levels of the efficacy, identity, and values (i.e., social influence processes) and higher levels of social influence processes, particularly science identity, lead to higher levels of persistence [ 62 , 64 , 65 ].…”
Section: Introductionmentioning
confidence: 99%
“…Second, the model has not been tested across a variety of critical time points in the academic career. For example, longitudinal mediation studies have primarily focused on students in the final two years of college and have only examined the indirect effects of social influence agents on integration through social influence processes [ 63 , 65 ]. National trends indicate that most departures from STEM majors occur during the first two years of college.…”
Section: Introductionmentioning
confidence: 99%
“…The research advisor role. There are various definitions of mentoring used in the life sciences, and different groups have different preferences on how to define mentoring in their research field (6,13,15,16,(22)(23)(24). The research literature on undergraduate-faculty mentoring relationships tends to highlight the mentor's role as an advisor to their mentee: (i) providing psychological and emotional support to the student, (ii) supporting the student in setting goals and choosing a career path, and (iii) acting as a role model (25).…”
Section: The Three Roles Of Research Faculty Towards Their Trainees: mentioning
confidence: 99%
“…Studies have shown that mentors are overall beneficial to career outcomes (26)(27)(28) and that psychosocial and career support, as well as role modeling, are integral to mentee success across gender and cultures, with the strongest effects coming from role modeling (23,(29)(30)(31). In the life sciences field, anyone overseeing a trainee can be referred to as a "mentor"; therefore, we will refer to this specific role of research faculty as that of a research advisor from here on and will use the term research mentor to refer to the three roles together (advisor, educator, supervisor).…”
Section: The Three Roles Of Research Faculty Towards Their Trainees: mentioning
confidence: 99%
“…Mentors must also consider larger issues of inclusivity and diversity when recruiting and hiring undergraduates (Carpi, Ronan, Falconer, & Lents, 2017;Hernandez et al, 2018;O'Donnell, Botelho, Brown, Gonzalez, & Head, 2015). Because research experience serves as such an important step in pursuing a career in STEM, mentors, as the gatekeepers, need to carefully consider their recruitment practices to ensure an equitable and inclusive process.…”
Section: Inclusivitymentioning
confidence: 99%